1981
DOI: 10.1017/s0031182000050149
|View full text |Cite
|
Sign up to set email alerts
|

Infections with blood parasites in the small British rodentsApodemus sylvaticus,Clethrionomys glareolusandMicrotus agrestis

Abstract: SUMMARYThree populations of small wild British rodents were studied by capture–recapture methods over a period of 3 years, a fourth group was studied for 1 year and a fifth was sampled annually for 4 years. Blood smears were taken from 3 species of rodents: the woodmouseA podemus sylvaticus, the bank voleClethrionomys glareolus(and an island sub-speciesC.g. skomerensis) and the short-tailed voleMicrotus agrestis. The smears were examined microscopically. Four genera of haemoparasitesBabesia, Hepatozoon, Trypan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
40
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 22 publications
(29 reference statements)
12
40
0
Order By: Relevance
“…Our results are in accordance to data from former Czechoslovakia, Austria and Great Britain (Šebek 1975, Šebek et al 1980, Frank 1978, Healing 1981, Turner 1986), but higher than from Norway (0-16.7% in summer -Wiger 1979). However, the infection with Herpetosoma trypanosomes depends on season (Turner 1986, Karbowiak andWita 2001).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are in accordance to data from former Czechoslovakia, Austria and Great Britain (Šebek 1975, Šebek et al 1980, Frank 1978, Healing 1981, Turner 1986), but higher than from Norway (0-16.7% in summer -Wiger 1979). However, the infection with Herpetosoma trypanosomes depends on season (Turner 1986, Karbowiak andWita 2001).…”
Section: Discussionsupporting
confidence: 91%
“…T. evotomys was relatively rare in bank vole in spring (0.9% -Šebek 1975, Šebek et al 1980) and frequent in late summer (Baker et al 1963, Karbowiak andWita 2001). The prevalence of T. microti was higher in root vole from Białowieża Forest (21.4-50.0%) than those noted for field vole (0.9-12.8% - Baker et al 1963, Šebek 1975, Healing 1981 and common vole Microtus arvalis (9.0% - Pawelczyk et al 2004). However, some authors showed the between-year variability in prevalence of this parasite (Wiger 1979, Pawelczyk et al 2004.…”
Section: Discussionmentioning
confidence: 87%
“…Seasonal (Wiger 1979, Turner 1986) and annual (Healing 1981) differences in the occurrence of blood forms of Hepatozoon have previously been reported from rodents in northern and Central Europe. In the present study, lung meronts were common in C. glareolus in all seasons (Table 1).…”
Section: Discussionmentioning
confidence: 83%
“…Intracellular gametocytes are found in circulation either in erythrocytes or in leukocytes. Surveys of small mammals in Central Europe (Mahnert 1972, Frank 1977, Šebek 1978, Šebek et al 1980, Walter and Liebisch 1980, Healing 1981, Turner 1986 indicate that Hepatozoon infections are especially common in the bank vole, Clethrionomys glareolus (Schreber). One species, Hepatozoon erhardovae Krampitz, 1964, has the bank vole as the type host.…”
mentioning
confidence: 99%
“…Human cases of babesiosis caused by B. microti in Europe are rarely described and were most likely acquired abroad (4). B. microti has also been documented as a parasite of rodents in different parts of Europe (5,7,22). The tick that is probably involved in maintenance of B. microti in rodent populations in Europe is Ixodes trianguliceps.…”
mentioning
confidence: 99%